Diels Alder Polyphenylene Anion Exchange Membrane for Nonaqueous Redox Flow Batteries. Issue 1 (23rd October 2015) - Small, Leo J.; Pratt, Harry D.; Fujimoto, Cy H.; Anderson, Travis M.
Abstract : Here highly conductive, solvent-resistant anionic Diels Alder polyphenylene (DAPP) membranes were synthesized with three different ionic contents and tested in an ionic liquid-based nonaqueous redox flow battery (RFB). These membranes display 3–10× increase in conductivity in propylene carbonate compared to some commercially available (aqueous) anion exchange membranes. The membrane with an ion content of 1.5 meq/g (DAPP1.5) proved too brittle for operation in a RFB, while the membrane with an ion content of 2.5 meq/g (DAPP2.5) allowed excessive movement of solvent and poor electrochemical yields (capacity fade). Despite having lower voltage efficiencies compared to DAPP2.5, the membrane with an intermediate ion content of 2.0 meq/g (DAPP2.0) exhibited higher coulombic efficiencies (96.4% vs. 89.1%) and electrochemical yields (21.6% vs. 10.9%) after 50 cycles. Crossover of the electroactive species was the primary reason for decreased electrochemical yields. Analysis of the anolyte and catholyte revealed degradation of the electroactive species and formation of a film at the membrane-solution interface. Increases in membrane resistance were attributed to mechanical and thermal aging of the membrane; no chemical change was observed. Improvements in the ionic selectivity and ionic conductivity of the membrane will increase the electrochemical yield and voltage efficiency of future nonaqueous redox flow batteries.